Acute kidney injury as initial presentation of renal lymphoma: Diagnostic and therapeutic challenges in a resource-limited setting - Aminde, Jeannine Anyingu (SAGE Open Med Case Rep, 2019)
Non-Hodgkin’s lymphoma is reportedly common in Africa; however, there is limited data on renal involvement. Acute kidney injury only at presentation is rare for lymphoproliferative malignancies. A 7-year old presented to our facility with a 2-week history of progressive abdominal distension and pain, examination revealed anasarca and hypertension. On further evaluation, there were bilateral nephromegaly, acute kidney injury (AKI) and cytomorphological findings suggestive of lymphoma. Patient management was mostly supportive, and evolution was unfavourable leading to his demise. We discuss diagnostic and therapeutic challenges due to unavailability of state-of-the-art facilities in resource-constrained settings.